Kontribusi Budaya dalam Negeri bagi Pendidikan guna Membentuk Karakter Peserta Didik - Sukmawati, Anis; Rahmawati, Sustania; Rohmah, Riza Mi’Rotul (Lembaga Yasin AlSys, 2023)
Education is the most important element in efforts to build a nation, because education is the gateway to a human being's intelligence. Education is not only about mathematics or science, education is more than that. Character building of students is an important element in education. The current generation can be said to have low environmental sensitivity so that it has an impact on how they behave with other humans. One way that can change the character of a person is to introduce him to culture, which is an advantage that this Indonesian nation has. Culture is something that is done continuously and then unconsciously becomes a habit. Character can also be changed if you do the same thing continuously and in this discussion through culture.